Structural or functional defects of PTEN in urothelial cells lacking P53 drive basal/squamous-subtype muscle-invasive bladder cancer. (1st December 2022) - He, Feng; Zhang, Fenglin; Liao, Yi; Tang, Moon-shong; Wu, Xue-Ru
Abstract: Muscle-invasive bladder cancer (MIBC) exhibits strong inter- and intra-tumor heterogeneity that affects biological behaviors, therapeutic responses, and prognoses. Mutations that activate RTK-RAS-PI3K and inactivate P19-P53-P21 coexist in 60–70% of MIBC. By time-controlled ablation of Tp53 and Pten, singly or combined, in adult mouse urothelium, we found that Tp53 loss alone produced no abnormality. While Pten loss elicited hyperplasia, it synergized with Tp53 loss to trigger 100% penetrant MIBC that exhibited basal/squamous features that resembled its human counterpart. Furthermore, PTEN was inactivated in human MIBC cell lines and specimens primarily by hyperphosphorylation of the C-terminus. Mutated or tailless PTEN incapable of C-terminal phosphorylation demonstrated increased inhibition of proliferation and invasion than full-length PTEN in cultured MIBC cells. In xenograft and transgenic mice, tailless PTEN, but not full-length PTEN, prevented further growth in established tumors. Collectively, deficiencies of both PTEN and P53 drive basal/squamous subtype MIBC. PTEN is inactivated by C-terminal hyperphosphorylation, and this modification may serve as a biomarker for subtyping MIBC and predicting tumor progression. Tailless PTEN is a potential molecular therapeutic for tumors, such as bladder cancer (BC), that can be readily accessed. Highlights: Bi-allelic loss of Tp53 / PTEN critical for muscle-invasive bladder cancer (MIBC). MIBC caused by Tp53 and Pten loss belongs to basal/squamous molecular subtype. PTEN is inactivated in bladder cancer primarily by C-terminal hyperphosphorylation. Phosphorylated PTEN a better biomarker for advanced bladder cancer than PTEN. Tailless PTEN is a potential molecular therapeutic for bladder cancer.